1979
DOI: 10.1007/bf00043546
|View full text |Cite
|
Sign up to set email alerts
|

Food preferences of tanypodinae larvae (Diptera: Chironomidae)

Abstract: Analyses of the gut contents of larvae of three species of Tanypodinae, collected from four sites in north-east England and Scotland, invariably showed small particles (1-1o µm2), predominantly of detritus, to be more abundant than large particles (totoo AM), mostly algae and diatoms . No animal remains, such as carapaces, head capsules and chaetae, or vascular plant fragments were found in any of the intestines . In contrast, food-choice and growth experiments suggested that animal food (particularly Tubifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 2 publications
3
31
0
1
Order By: Relevance
“…High proportions of Tanypodinae automatically reduce the proportions of other taxa, even if their densities have not changed. In addition, however, Tanypodinae are usually considered to be predatory taxa, although few are obligate carnivores (Roback, 1969;Oliver, 1971;Baker and McLachlan, 1979;Walker et al, 1985). Ablabesymia and Thienemannimyia group make up the bulk of the tanypods at Hawes Water, and Darby (1962), Roback (1969), Baker and McLachlan (1979) and Merritt and Cummins (1996) consider these to be essentially carnivorous, including in their diet other chironomids; other material may be exploited when prey items are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…High proportions of Tanypodinae automatically reduce the proportions of other taxa, even if their densities have not changed. In addition, however, Tanypodinae are usually considered to be predatory taxa, although few are obligate carnivores (Roback, 1969;Oliver, 1971;Baker and McLachlan, 1979;Walker et al, 1985). Ablabesymia and Thienemannimyia group make up the bulk of the tanypods at Hawes Water, and Darby (1962), Roback (1969), Baker and McLachlan (1979) and Merritt and Cummins (1996) consider these to be essentially carnivorous, including in their diet other chironomids; other material may be exploited when prey items are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this genus is classified as a predator in temperate regions but in this study we classified it as omnivorous. Some diet analysis concluded that, under certain conditions, species of Chironomidae may utilize a wider range of trophic resources (Baker & McLachlan, 1979;Motta & Uieda, 2004;Galizzi et al, 2012;Saito & FonsecaGessner, 2014;Butakka et al 2014). Our results pointed out that, because of its wide trophic spectrum, Monopelopia sp.…”
Section: Discussionmentioning
confidence: 54%
“…are known to be predators (KONSTANTINOV, 1968cited in MOLLER PILLOT, 1984MONAKOV, 1972;TITMUS and 8ADCOCK, 1981). However, although Proc/adius has a preference for Tubiflcidae, it uses a large range of food items, the most important of which appears to be detritus (BAKER and McLACHLAN, 1979). Because chironomid densities in both reservoirs were similar, the difference in availability of Tubificidae had no influence.…”
Section: Discussionmentioning
confidence: 97%